2012
DOI: 10.4321/s0004-05922012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milking frequency on milk yield, dry matter intake and efficiency of feed utilization in WAD goats

Abstract: SUMMARYEffects of milking frequency on milk yield, dry matter intake (DMI) and effeciency of feed utilization for milk production was investigated in West African Dwarf (WAD) goats at Abeokuta in the humid zone of South Western Nigeria. Seventeen WAD goats were fed a ration comprising (on dry matter basis) 50% grass (Pennisetum purpureum) and 50% concentrate (17% crude protein) at 5% body weight. The study involved hand milking once (at 6.00 am), twice (at 6.00am and 6.00pm) and thrice (at 6.00 am, 2.00 pm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In support of the current results, [ 16 ] previously studied the effects of milking frequency on production efficiency in Holstein cows and found that milking three times daily increased milk yield and DMI. In another study, [ 17 ] asserted that DMI increases (p < 0.05) with greater milking frequency. The current results are also supported by previous works ([ 16 , 18 , 19 ]) in which increased DMI was shown to be accompanied by higher milk yield due to greater milking frequency.…”
Section: Resultsmentioning
confidence: 99%
“…In support of the current results, [ 16 ] previously studied the effects of milking frequency on production efficiency in Holstein cows and found that milking three times daily increased milk yield and DMI. In another study, [ 17 ] asserted that DMI increases (p < 0.05) with greater milking frequency. The current results are also supported by previous works ([ 16 , 18 , 19 ]) in which increased DMI was shown to be accompanied by higher milk yield due to greater milking frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The values obtained in this study on the efficient of utilization of feed by the goats for milk production are within the ranges obtained by other authors. Williams et al (2012) reported efficiency of feed utilization for milk production of 0.237-0.431 in Wad goats. The efficient utilization of feed by the ruminants may possibly be accredited to the physiological status, breed of the animals and the quality of the ration offered.…”
Section: Resultsmentioning
confidence: 99%
“…Breast milk can also be viewed as a raw material that contains a source of essential food substances. According to Williams et al (2012), the main constituents are water, protein, fat, carbohydrates, minerals, and vitamins. Milk is the largest component because 87% of all elements of milk consist of water.…”
Section: Water Contentmentioning
confidence: 99%
“…Other factors that affect milk's water content and chemical compositions are the quality and quantity of rations and drinking water. According to Williams et al (2012), milk production is influenced by factors: type of livestock, level of lactation, age of cattle, injection of inflammation in the udder, livestock nutrition, environment, and milking procedures.…”
Section: Water Contentmentioning
confidence: 99%